The Influence of Education and Home Environment on the Cognitive Development of Preschool Children in Owerri West Local Government Area IMO State - Nnorom, Stanley; Helen, Enwezor Chibuogwu; Stephen A., Ezenwagu; Nwankwo, Benignus C. (International Journal For Research In Educational Studies, 2021)
Educational imbalance is adhering to accepted standards issues among the scientific community in African countries. The psychological characteristics that distinguish one person from another and thus help to define each person's individuality emerge well before children arrive at school. Moreover, the following analysis deals with the explanation of early differences in cognitive outcomes. However, there is much research done in the world and in Nigeria to be precise on the subject matter. The main question is if the influence of the educational background and the home environment has strong effects on the cognitive development of Preschool children. This study was designed to investigate the influence of education and home environment on the cognitive development of preschool children in Owerri west Local Government Area of Imo State, Nigeria. The study confirms that home environment and the education of the parents are important for children's outcomes at the age. In addition both factors also play a major role for the explanation of the improvement of cognitive abilities. The results show that in Owerri West, the home environment and parental education are important predictors of cognitive abilities. As a main result the study shows that it is very important to control for earlier abilities of the children and to encourage low educated parents to be active with their children, since in that way they can compensate for their lower educational background.